1998
DOI: 10.1073/pnas.95.22.13221
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of matrix metalloproteinase-9 and inhibition of tumor invasion by the membrane-anchored glycoprotein RECK

Abstract: A human fibroblast cDNA expression library was screened for cDNA clones giving rise to f lat colonies when transfected into v-Ki-ras-transformed NIH 3T3 cells. One such gene, RECK, encodes a membrane-anchored glycoprotein of about 110 kDa with multiple epidermal growth factor-like repeats and serine-protease inhibitor-like domains. While RECK mRNA is expressed in various human tissues and untransformed cells, it is undetectable in tumor-derived cell lines and oncogenically transformed cells. Restored expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
554
3
53

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(631 citation statements)
references
References 33 publications
21
554
3
53
Order By: Relevance
“…• Epithelial-mesenchymal transition (EMT) [134][135][136][137][138] • Invasion and metastasis 29,138,139 • Vasoconstriction 140…”
Section: Box 2 Biological Consequences Of Mmp Proteolysismentioning
confidence: 99%
“…• Epithelial-mesenchymal transition (EMT) [134][135][136][137][138] • Invasion and metastasis 29,138,139 • Vasoconstriction 140…”
Section: Box 2 Biological Consequences Of Mmp Proteolysismentioning
confidence: 99%
“…Reversion-inducing cysteine-rich protein with Kazal motifs (RECK) acts as a membrane-anchored metalloproteinase regulator [1][2][3][4] which functions as a regulator of extracellular matrix integrity in normal condition, contributing to tumor and metastasis suppressing agent. However, recent study found abundant expression of RECK in the cells associated with blood vessels undergoing rapid remodeling in the mouse implantation chambers, suggesting that RECK has a role in vascular remodeling which may involve non-sprouting mechanisms such as intussusception and pruning.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, subsequent evidence suggested that subdomain IV of the extracellular domain is important for dimerization and small peptides with cysteine knot topology is able to block dimer formation of HER-2/Neu [18]. RECK protein contains five putative cysteine knot motifs at the NH 2 -terminal region [1]. Therefore, RECK may use this region to interfere HER-2/ Neu dimer formation.…”
Section: Resultsmentioning
confidence: 99%
“…RECK was originally identified as a MMP inhibitor with little anti-proliferative activity on various tumor-derived cell lines, including HT1080 (sarcoma), B16 (melanoma), SW48 (colon cancer), A549 (lung cancer), HeLa (cervical cancer), and A673 (Ewing tumor) [1]. However, a recent study demonstrated that knockdown of RECK in human umbilical vein endothelial cells induced growth arrest and cellular senescence [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation